Pro Couchbase Server - Ostrovsky, David. (Apress : Imprint: Apress, 2015)
This new edition is a hands-on guide for developers and administrators who want to use the power and flexibility of Couchbase Server 4.0 in their applications. The second edition extends coverage of N1QL, the SQL-like query language for Couchbase. It also brings coverage of multiple new features, including the new generation of client SDKs, security and LDAP integration, secondary indexes, and multi-dimensional scaling. Pro Couchbase Server covers everything you need to develop Couchbase solutions and deploy them in production. The NoSQL movement has fundamentally changed the database world in recent years. Influenced by the growing needs of web-scale applications, NoSQL databases such as Couchbase Server provide new approaches to scalability, reliability, and performance. Never have document databases been so powerful and performant. With the power and flexibility of Couchbase Server, you can model your data however you want, and easily change the data model any time you want. Pro Couchbase Server shows what is possible and helps you take full advantage of Couchbase Server and all the performance and scalability that it offers. Helps you design and develop a document database using Couchbase Server. Covers the latest features such as the N1QL query language. Gives you the tools to scale out your application as needed.